2008
DOI: 10.1016/j.jtcvs.2007.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted magnetic resonance imaging can be used in place of positron emission tomography for N staging of non–small cell lung cancer with fewer false-positive results

Abstract: Diffusion-weighted magnetic resonance imaging can be used in place of positron emission tomography-computed tomography for N staging of non-small cell lung cancer with fewer false-positive results compared with positron emission tomography-computed tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 19 publications
3
95
0
5
Order By: Relevance
“…Diffusion of water molecules in malignant tumors is usually restricted compared to that in normal tissue, resulting in a decreased apparent diffusion coefficient (ADC) value (Szafer et al, 1995;Takahara et al, 2004). Some recent studies comparing DWI with FDG-PET have shown that DWI at 1.5 T is comparable with FDG-PET for detecting malignant lesions (Komori et al, 2007;Nomori et al, 2008;Mori et al, 2008), and an meta-analysis has shown that DWI can be used to differentiate malignant from benign pulmonary lesions . It is uncertain whether DWI has advantages over FDG-PET for distinguishing malignant from benign pulmonary nodules and masses.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion of water molecules in malignant tumors is usually restricted compared to that in normal tissue, resulting in a decreased apparent diffusion coefficient (ADC) value (Szafer et al, 1995;Takahara et al, 2004). Some recent studies comparing DWI with FDG-PET have shown that DWI at 1.5 T is comparable with FDG-PET for detecting malignant lesions (Komori et al, 2007;Nomori et al, 2008;Mori et al, 2008), and an meta-analysis has shown that DWI can be used to differentiate malignant from benign pulmonary lesions . It is uncertain whether DWI has advantages over FDG-PET for distinguishing malignant from benign pulmonary nodules and masses.…”
Section: Introductionmentioning
confidence: 99%
“…Experience with thoracic applications of DWI techniques is still growing, and preliminary studies have reported promising results (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Thoracic Applicationsmentioning
confidence: 99%
“…In heterogeneous tumors, care should be taken to place the ROI in the solid portion of the mass, excluding cystic or necrotic areas. DWI has been used to characterize lung lesions (27), to detect and classify adenocarcinomas (37), to predict tumor invasiveness in early-stage lung cancer (24), to detect tumors in collapsed lungs (32,33), and for nodal staging of lung cancer (26,35).…”
Section: Thoracic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors have less diffusion of water due to increased cellularity, more macromolecular proteins and less extracellular space and hence lower apparent diffusion coefficient [22]. Nomori et al reported lower rate of false positives (FPs) and a higher accuracy of diffusion-weighted imaging MRI as compared with PET-CT in mediastinal staging of NSCLC [23], but these results have not been replicated by others [24]. Further work is needed to determine whether this technology will be useful in routine mediastinal staging of NSCLC.…”
Section: Mrimentioning
confidence: 99%